The Influence of Principal Leadership, Productive Teacher Training, Work Commitment and Motivation on Performance Management of Productive Vocational School Teachers in North Sulawesi Province - Harold F.K Tambajong; J.A.M. Rawis; Jeffry S.J Lengkong; Treesje K. Londa (Peneliti.net, 2020)
This study aims to determine the influence of the principal's leadership, productive teacher training, commitment, and work motivation on the performance management of productive teachers of vocational schools in North Sulawesi Province who hold light vehicle engineering skills competencies totaling 722 teachers. This study uses a quantitative approach with a survey method with causality study techniques and uses path analysis. The research data were collected using a questionnaire technique and analyzed. The population in this study were vocational teachers in North Sulawesi Province. The determination of the number of samples in this study was carried out by multi-stage sampling using the Slovin formula to obtain 264 teachers. Based on the results of research, principal leadership has a positive effect on productive teacher professional training, this shows that the higher the leadership of the principal, the more productive teacher professional training for vocational teachers in North Sulawesi Province will beBased on the conclusion that the leadership of the principal has a positive effect on productive teacher professional training, commitment and work motivation of productive teachers, this shows that the higher the leadership of the principal, the more productive teacher performance management of vocational teachers in 15 North Sulawesi Province will be improved.